Nationalism, cosmopolitanism and empire in Britain's American expatriate community, c.1815–1914. - Tuffnell, S (2013)
This study examines the coalescence of American expatriate communities in Britain between 1815 and 1914. Blending transnational and post-colonial approaches to US history, this dissertation explores the nuanced roles of Americans in Britain as intermediaries in the consolidation of US independence, the formation of American nationalism, and the emergence of American empire. Transatlantic economic and cultural connections converged in American communities in Britain. The American communities of London and Liverpool evolved and dissolved around these rapidly transforming interconnections. These communities are recaptured in this study from scattered archives on both side of the Atlantic. The Antebellum American community acted as a conduit between British capital and American nation-building projects and promoted transatlantic rapprochement as the route to effective US independence. The importation of American innovation and manufactured goods into Britain and the Empire, however, followed late nineteenth-century expatriates. As US power surged, Americans in London created a self-identifying American “colony,” which acted as the interface between US economic and cultural expansion and British imperialism. Throughout the century, Britain’s American communities acted as crucibles in which sectional, national, and racial identifications were contested and reconstructed. Expatriate newspapers, celebrations, and social institutions, provided the venues for Americans in Britain to articulate and reformulate American nationalism. In the context of British power, the contestations and reformulations of these identities were bled through with post- and anti-colonial anxieties. Expatriates therefore acted as avatars for sharpening distinctions between the US and Britain in debates over the form of American national character, culture, and empire – and Britain’s role in all three. This study reframes these themes around the previously overlooked communities of Americans in Britain. From these communities, which stand at the intersection of US and British Imperial history, a new perspective emerges on the reciprocal dynamics of nationhood and empire in nineteenth century Anglo-American relations.